Perbedaan agresivitas pada anak usia dini yang dibacakan dongeng dengan yang tidak dibacakan dongeng sebelum tidur oleh ibu - Dian Jayantari Putri K Hedo; Hilda Sudhana (Jurnal Psikologi Udayana, 2014)
Aim of this research is to know about difference of aggression in young children that get fairytales reading and in young children that don’t get fairytales reading before sleep from their mother. Aggression has been a problem many people talk about, especially about its cause, or its intervention. Every people has aggression, including young children. People believe that young children’s aggression isn’t dangerous, so they only focus doing interventions in adult or adolescence aggression and disregard interventions in childhood aggression. Actually, it’s better to do intervention in young children, for it prevents long term negative impact of aggression. One of the interventions in controlling aggression is read fairytales to children. Fairytales give children good impacts that related to the aggression’s causes. Fairytales-reading is familiar thing in Indonesian culture. According to that, researcher formulates a research’s problem, that is, is there difference of aggression in young children that get fairytales reading and in young children that don’t get fairytales reading before sleep from their mother. Research’s subjects are 92 mothers of young children from kindergartens in Denpasar. Research’s method is comparation research. Data are collected by questionnaire (aggression scale and fairytale reading’s categorization). Validity test of aggression scale find 6 invalid items and 68 valid items from 74 items, with reliability coefficient’s score is 0,989. Data are analyzed with independent sample t-test. Data analysis’s result shows that data are normal and homogen. Score of significant in t-test is 0,000 (p=0,05). It means that research’s hypothesis who state there is difference of aggression in young children that get fairytales reading and in young children that don’t get fairytales reading before sleep from their mother, is accepted. Categorization of aggression’s score shows that children who receive fairytales reading have lower score than children who don’t receive fairytales reading. Keywords: aggression, fairytales, early childhood, mother